Self-awareness in the formation of the future music teacher’s scientific research culture - Tusheva, Victoria (Professional Art Education, 2022)
The purpose of the article is to highlight the functional characteristics of future music teacher’s selfawareness and worldview orientations as determinants of his scientific and research culture formation. Methods and methodology. The ideas of H.S.Kostyuka, S.D.Maksimenko, S.L.Rubinstein regarding the understanding of the ontology of mental phenomena, generalized by the principle of the unity of consciousness and activity, the development of professionally important qualities of the individual in the systemogenesis of activity; as well as the position of higher art education in relation to cultural, personality-oriented, systemic approaches as a methodological basis in revealing the peculiarities of the future teacher-musician’s self-awareness have acquired methodological significance for the selected issue. The scientific novelty of the article consists in illumination of the purpose of the professional worldview activity and in the context of the teacher-musician scientific research culture, the revealing of the essence of teachermusician self-awareness, the formation of which is manifested as support for its internal consistency and self-identity, the construction of conscious research and pedagogy; self-knowledge and search for the meaning of life through selfimprovement, self-understanding, self-education by means of research in the field of art education. The results. The theoretical-methodological aspects of the problem of future teachers-musicians’ scientificresearch culture formation are revealed, and in particular, issues regarding their self-awareness, semantic-forming and professional worldview activities. The scientific research culture of the future teacher-musician is defined as a dynamic, integrative quality of the personality, manifested in the ability to synthesize analytical-synthetic, inductive-deductive mental activity and emotional-figurative comprehension of musical art, the embodiment of scientific, pedagogical and artistic. application of scientific knowledge in pedagogical activity as a scientific-theoretical (explanatory) and constructive-technological (transformative) function. It is noted that the teacher’s self-awareness ensures the tension of his intellect, worldview intentions, social determinism of scientific research in musical and pedagogical education. It is emphasized that a particular importance of the researcher’s semantic-forming activity is acquired by the worldview, which is characterized by spiritual and aesthetic content and orientation, which is manifested as a valuable attitude to socio-cultural, educational and pedagogical processes through the prism of personal worldview. It was concluded that the result of the formation of future teacher-musician’s scientific and research culture is formed qualitative and instrumental properties of self-awareness, which ensure its functioning.